Never Enough Time: A Practical and Spiritual Guide - Schaper, Donna (Rowman & Littlefield Publishers, 2018)
Most of us struggle with the “time famine”—the pervasive feeling of never having enough time. Whether we work three jobs or none, have many children or none, or live in a huge city or a small town, most of us have the feeling there is always more to do than we’re able, more time required than we can give. In Never Enough Time,Rev. Donna Schaper helps us think through the practical and spiritual elements of the time famine and helps us instead aim for a feast. Schaper’s advice centers around our mind-set—understanding both the structural and personal reasons we feel so pressed, clarifying what’s important to us or not, and setting realistic expectations, while enriching the time we have. The book goes beyond the idea of “Sabbath keeping” to offer suggestions for all parts of life—particularly the busy moments. Schaper draws on her years ministering to people across all walks of life to show that the time famine cuts across race, class, and gender lines to touch almost everyone. She offers practical and spiritual suggestions that won’t magically give us more time, but can help us live better with the time we have.